2006
DOI: 10.1016/j.socscimed.2006.06.029
|View full text |Cite
|
Sign up to set email alerts
|

“A lot of sacrifices:” Work–family spillover and the food choice coping strategies of low-wage employed parents

Abstract: Integrating their work and family lives is an everyday challenge for employed parents. Competing demands for parents' time and energy may contribute to fewer meals prepared or eaten at home and poorer nutritional quality of meals. Thus, work-family spillover (feelings, attitudes, and behaviors carried over from one role to another) is a phenomenon with implications for nutrition and health. The aim of this theory-guided constructivist research was to understand how low-wage employed parents' experiences of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
204
3
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(221 citation statements)
references
References 49 publications
13
204
3
1
Order By: Relevance
“…Confounding is unlikely to account for these observed relationships, which in our study hold true even when controlling for factors such as race/ethnicity Table 3; all differences were significant at P , 0?001 by the Wald x 2 test (GED, general equivalency degree) and family structure. Previous studies have shown that time is a significant barrier preventing many people from cooking, and this is especially true among low-SES groups (10)(11)(12) . Our work further explains these observations by showing that compared with high-SES groups, low-SES groups have a more dichotomous (never/always) distribution when it comes to cooking.…”
Section: Discussionmentioning
confidence: 99%
“…Confounding is unlikely to account for these observed relationships, which in our study hold true even when controlling for factors such as race/ethnicity Table 3; all differences were significant at P , 0?001 by the Wald x 2 test (GED, general equivalency degree) and family structure. Previous studies have shown that time is a significant barrier preventing many people from cooking, and this is especially true among low-SES groups (10)(11)(12) . Our work further explains these observations by showing that compared with high-SES groups, low-SES groups have a more dichotomous (never/always) distribution when it comes to cooking.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research has indicated that time constraints and the use of convenience foods are interrelated, and are also influenced by family dynamics, such as the number of adults within the household and external stressors such as work commitments (33,34) . Perceived time pressures were noted as being important in the purchase of takeaway meals in Ireland (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these foods are often high in fat and sugar and children become accustomed to them, hence developing a preference. [26,27] This could result in the younger generations acquiring fewer cooking skills from their mothers and, in turn, a reliance on convenience foods.…”
Section: Discussionmentioning
confidence: 99%
“…The food industry has responded and capitalised on this need, but the majority of options still focus on convenience and not on health. [27,28] The value of changing supermarket layout to enhance the visibility of healthier items justifies further exploration. Participants in a study conducted by Zacchary et al [29] suggested having taste test sections to increase consumer confidence in a product.…”
Section: Discussionmentioning
confidence: 99%